PENGELOLAAN MADRASAH PADA PESANTREN DI PONDOK PESANTREN AL FALAH PUTERA BANJARBARU - Muhamad Ramli (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2018)
This study aims to reveal about the management of madrasah in pesantren in Pondok Pesantren Al Falah Putera Banjarbaru in terms of organizing, implementation of education and curricular programs, and supervision. This research uses qualitative approach with research subject are leader of Pesantren Al Falah Putera Banjarbaru, Head of Madrasah every education level held at Pondok Pesantren Al Falah Putera Banjarbaru, that is Head of Madrasah Aliyah Al Falah Putera, Head of Madrasah Tsanawiyah Al Falah Putera, board of curriculum , student affairs officers, administrative division, teachers and students at madrasah in Pondok Pesantren Al Falah Putera. Data collection is done by observation, interview and document analysis. The validity of data is done by extending the time of research and triangulation. Data analysis technique used is with interactive analysis model. The results showed that; The management of madrasah at pesantren in Pondok Pesantren Al Falah Putera viewed from the organizing aspect, this pesantren has organizational structure from the top level to the bottom with accompanied by clear delegation of authority and responsibility so that every member can work efficiently. The delegation has also been running well so that the organization can use its resources efficiently. As for the management of madrasah in pesantren in Pondok Pesantren Al Falah Putera viewed from curricular exercise, in this pesantren curricular program development has been going well, because between curricular madrasah with curricular pesantren has been systematized in accordance with the basic framework of pesantren development since its inception. With systematized every activity undertaken concerning curricular program between madrasah and pesantren become easily synchronized, so that can minimize conflict which can disrupt work climate and organization of boarding school. Then viewed from the aspect of supervision, boarding school Al Falah can easily control and supervise all activities of the santri, because between boarding activities with madrassas have been well structured, according to ladder and time. There are four elements that conduct supervision for the smoothness of learning activities in this pesantren, the four elements are; leader of Pesantren, coordinators/head of Madrasah, ustadz/teachers, seneor santri/students.